2018
DOI: 10.1016/j.jsbmb.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol metabolites as biomarkers of endometrial cancer prognosis after surgery

Abstract: Endometrial cancer (EC) is the most common gynecologic malignancy prevailing after menopause. Defining steroid profiles may help predict the risk of recurrence after hysterectomy, which remains limited due to the lack of reliable markers. Adrenal precursors, androgens, parent estrogens and catechol estrogen metabolites were measured by mass spectrometry (MS) in preoperative serums and those collected one month after hysterectomy from 246 newly diagnosed postmenopausal EC cases. We also examined the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…These have been associated with EC and breast cancer progression, supporting the role of bradykinin in tumors originating from steroid sensitive tissues (39,40). Sulfated androgens were also higher in type I EC cases, consistent with the reported implication of sulfated steroids in this histotype (8,(41)(42)(43)(44). Furthermore, our data identified heme as a putative biomarker of type II EC and highlighted modifications in pathways closely related to heme synthesis, namely the tetrahydrofolate-serine/glycine pathway (45).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These have been associated with EC and breast cancer progression, supporting the role of bradykinin in tumors originating from steroid sensitive tissues (39,40). Sulfated androgens were also higher in type I EC cases, consistent with the reported implication of sulfated steroids in this histotype (8,(41)(42)(43)(44). Furthermore, our data identified heme as a putative biomarker of type II EC and highlighted modifications in pathways closely related to heme synthesis, namely the tetrahydrofolate-serine/glycine pathway (45).…”
Section: Discussionsupporting
confidence: 84%
“…Bile acids contribute to cholesterol homeostasis, a precursor of the steroids that drive the development and progression of this histological type of EC (10). Recently, we showed that higher levels of circulating steroids are linked to an increased risk of recurrence (43). Numerous enzymatic pathways are involved in the conversion of both bile acids and steroids, including reduction by aldo-keto reductases (49), conjugation by uridine diphospho-glucuronosyltransferases (50), sulfotransferases (51), and sulfatase (52).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids contribute to cholesterol homeostasis, a precursor of the steroids that drive the development and progression of this histological type of EC ( 10 ). Recently, we showed that higher levels of circulating steroids are linked to an increased risk of recurrence ( 43 ). Numerous enzymatic pathways are involved in the conversion of both bile acids and steroids, including reduction by aldo-keto reductases ( 49 ), conjugation by uridine diphospho-glucuronosyltransferases ( 50 ), sulfotransferases ( 51 ), and sulfatase ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, EC has a good prognosis with 78% of patients achieving 10-year survival [ 1 ]. Currently, our only methods of determining which patients are more likely to suffer poor outcomes include clinicopathological features such as tumour grade, histological subtype and clinical stage [ 2 ]. Hysterectomy with or without adjuvant radiotherapy is curative for most patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy with or without adjuvant radiotherapy is curative for most patients. However, a small subset of patients will develop a disease recurrence that fails to respond to chemotherapy and thus experience shorter survival [ 2 ]. This group has proven difficult to identify at diagnosis, therefore a novel prognostic marker may be of particular benefit for these patients.…”
Section: Introductionmentioning
confidence: 99%